2018
DOI: 10.1111/jnc.14465
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of TAR DNA‐binding protein 43 isoforms depends on their submitochondrial localization in neuronal cells

Abstract: TAR DNA-binding protein 43 (TDP-43) is an RNA-binding protein and a major component of protein aggregates found in amyotrophic lateral sclerosis and several other neurodegenerative diseases. TDP-43 exists as a full-length protein and as two shorter forms of 25 and 35 kDa. Full-length mutant TDP-43s found in amyotrophic lateral sclerosis patients re-localize from the nucleus to the cytoplasm and in part to mitochondria, where they exert a toxic role associated with neurodegeneration. However, induction of mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 39 publications
(59 reference statements)
4
39
0
3
Order By: Relevance
“…Indeed, there is evidence to suggest that TDP-43 regulates glycolysis in hepatocellular carcinoma cell lines [ 131 ], and one study demonstrated that the abnormal localization of TDP-43 to mitochondria in cells from ALS/FTLD patients leads to the disassembly of the respiratory chain complex I and impairs mitochondrial oxidative phosphorylation [ 181 ]. This has been corroborated by two more studies showing a pathological displacement of TDP-43, or its N- and C-terminal fragments, in mitochondria leading to impairment of mitochondrial functioning [ 34 , 153 ]. Hyperglycemia could counteract this by providing more substrate (glucose) for cellular glucose metabolism, thereby partially replenishing the ATP deficit.…”
Section: Does Altered Metabolism Counteract Effects Of Protein Aggregmentioning
confidence: 68%
“…Indeed, there is evidence to suggest that TDP-43 regulates glycolysis in hepatocellular carcinoma cell lines [ 131 ], and one study demonstrated that the abnormal localization of TDP-43 to mitochondria in cells from ALS/FTLD patients leads to the disassembly of the respiratory chain complex I and impairs mitochondrial oxidative phosphorylation [ 181 ]. This has been corroborated by two more studies showing a pathological displacement of TDP-43, or its N- and C-terminal fragments, in mitochondria leading to impairment of mitochondrial functioning [ 34 , 153 ]. Hyperglycemia could counteract this by providing more substrate (glucose) for cellular glucose metabolism, thereby partially replenishing the ATP deficit.…”
Section: Does Altered Metabolism Counteract Effects Of Protein Aggregmentioning
confidence: 68%
“…Despite our data, impaired mitochondrial function was shown to be closely related to ALS pathophysiology (Muyderman and Chen, 2014). Mitochondrial dysfunction is another toxic effect mediated by TDP-43 according to independent reports [23,24], and TDP-43 colocalization in the mitochondria seems to be essential for this deleterious effect [25,26].…”
Section: Tdp-43 Overexpression and Mitochondrial Functionmentioning
confidence: 91%
“…Evaluation of mitochondrial bioenergetics was performed by Seahorse XF96 Extracellular Flux Analyzer (Seahorse Bioscience‐Agilent, USA). Multiple parameters of mitochondrial function were measured with Stimulus XF Stress Test Kit (Seahorse Bioscience) . Briefly, differentiated NSC‐34 cells were seeded (7 × 10 4 cells/well) into micro‐lysine‐coated XF96 microplates and incubated overnight in 5% CO 2 , 37 °C.…”
Section: Methodsmentioning
confidence: 99%